Pengaruh Kualitas Produk, Harga dan Citra Merek Terhadap Keputusan Pembelian pada Smartphone Merek Iphone - Tasya Indria Putri (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
This research discusses the magnitude of the influence of product quality, price, brand image on purchasing decisions on Iphone brand smartphones. The purpose of this study was to determine the relationship between price, product quality, and brand image on purchasing decisions for Iphone brand smartphones. This study uses quantitative research using a questionnaire as a research test method. The population in this study were Iphone brand smartphone users in the Jakarta, Bogor, Depok, Tangerang and Bekasi areas. The sample in this study amounted to 135 respondents. The analytical tool used in this study is multiple linear regression with validity testing using Product Moment correlation and reliability testing using Cronbach Alpha. The findings in this study indicate that all variables used in this study have a positive effect on purchasing decisions. Product quality has a positive effect on purchasing decisions, price has a positive effect on purchasing decisions and brand image has a positive effect on purchasing decisions. The results of this study are expected to provide an overview of the aspects that can influence purchasing decisions on Iphone brand smartphones so that they can be useful for consumers and further research.